2017
DOI: 10.2147/clep.s145264
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyle behavior and risk of long duration troublesome neck pain or low back pain among men and women: results from the Stockholm Public Health Cohort

Abstract: BackgroundThe role of healthy lifestyle behavior (HLB) in terms of physical activity, alcohol intake, smoking, and diet put together has not yet been explored for the risk of low back pain (LBP) and neck pain (NP). Our aim was to study if an HLB is protective against the onset of long duration troublesome LBP and NP in men and women.MethodsTwo cohorts from the Stockholm Public Health Cohort, free from LBP (n=12,483) and NP (n=10,539), respectively, in 2006, were surveyed with questionnaires. Baseline informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
(47 reference statements)
0
22
0
Order By: Relevance
“…Similarly, our findings suggested a relationship between sleep time and subjective symptoms of SN/S and LBP, and sleep time seems an important factor in preventing symptom development. Furthermore, previous studies have reported that lower physical activity during leisure time and exercise habits reduce neck and low back pain risk ( Hartvigsen and Christensen, 2007 , Björck-van et al, 2008 , Skillgate et al, 2017 , Kirsch et al, 2019 ). Similarly, our findings suggested a relationship between exercise habits and subjective symptoms of SN/S and LBP.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, our findings suggested a relationship between sleep time and subjective symptoms of SN/S and LBP, and sleep time seems an important factor in preventing symptom development. Furthermore, previous studies have reported that lower physical activity during leisure time and exercise habits reduce neck and low back pain risk ( Hartvigsen and Christensen, 2007 , Björck-van et al, 2008 , Skillgate et al, 2017 , Kirsch et al, 2019 ). Similarly, our findings suggested a relationship between exercise habits and subjective symptoms of SN/S and LBP.…”
Section: Discussionmentioning
confidence: 98%
“…However, it was not clarified which lifestyle changes should be prioritized. Moreover, a recent study clarified the relationship between lifestyle behaviors (e.g., intensity of physical activity, smoking daily or not, alcohol, fruit, and vegetable intake) and neck or low back pain ( Skillgate et al, 2017 ). However, the studies have not examined lifestyle factors common to the neck and low back pain.…”
Section: Introductionmentioning
confidence: 99%
“…The development and testing of innovative methods to include lifestyle interventions for neck pain is needed. It is known that many lifestyle factors are associated with chronic musculoskeletal pain including physical activity [60], sleep [92], smoking [93], stress [94,95], and possibly diet [96]. At the current time, it is not known if addressing these factors will prevent the development of neck pain or the transitions to recovery once an injury has occurred [97].…”
Section: Promising Directions For Researchmentioning
confidence: 99%
“…Hence, in summary it seems as adapting to a healthy lifestyle behaviour is beneficial in order to decrease the risk of a poor outcome both among persons with neck pain and persons with back pain. In another study, again within the Stockholm Public Health Cohort, but including persons free of neck pain and/or back pain in 2006, we found a healthy lifestyle behaviour to decrease the risk of developing long-duration troublesome neck pain among women, and a decreased risk of developing long-duration back pain among men 14…”
Section: Discussionmentioning
confidence: 71%
“…Our research group has previously focused on a healthy lifestyle behaviour, defined as following the health-enhancing recommendations for leisure time physically active, alcohol consumption, daily intake of fruit and vegetables and not smoking. We found that a healthy lifestyle behaviour reduces the risk of long-duration troublesome low back pain in men, and long-duration troublesome neck pain in women 14. We have also examined the influence of a healthy lifestyle behaviour in men and women with occasional low back pain, showing a decreased risk of long-duration troublesome low back pain in women, and indicating a decreased risk in men 15…”
Section: Introductionmentioning
confidence: 84%